Development of a system to predict the evolution of individual tree mature cork caliber over time - Almeida, Alice M.; Tomé, José; Tomé, Margarida (Forest Ecology and Management, 2010)
The development of a model for the prediction of the evolution of individual tree cork caliber over time, from a measurement taken at a certain point in time, was the main objective of this work. The model includes three sub-models: a model to predict the thickness of complete rings from cork caliber at tc years; a cork growth model (for complete rings) and a model to predict cork caliber at age tc from the corresponding thickness of (tc − 1) complete rings. The algebraic difference approach (ADA) as well as the generalized algebraic difference approach (GADA) were used in modeling cork growth. Several base models with one or two site-tree-speciﬁc parameters were ﬁtted to the data using the dummy variable approach. The selection of the cork growth model was based on several criteria: ﬁtting ability, prediction performance evaluated through the PRESS residuals and behaviour screened with available knowledge on the cork growth process. The ADA model derived from the log-logistic function with the asymptote as free parameter was selected. The models developed to predict cork caliber and the corresponding thickness of complete rings were based in the linear relationship between the two variables. The two models were simultaneously ﬁtted using two stage least squares approach. The predicted thickness of cork complete rings in a 9-year old cork is proposed as a cork growth index. The distribution of this index can be used to characterize the potential of a site for cork production.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Cork caliber; Cork growth index; Cork growth models; Cork thickness of complete rings